2021
DOI: 10.1021/acs.jcim.1c00241
|View full text |Cite
|
Sign up to set email alerts
|

Anchor-Locker Binding Mechanism of the Coronavirus Spike Protein to Human ACE2: Insights from Computational Analysis

Abstract: COVID-19 has emerged as the most serious international pandemic in early 2020 and the lack of comprehensive knowledge in the recognition and transmission mechanisms of this virus hinders the development of suitable therapeutic strategies. The specific recognition during the binding of the spike glycoprotein (S protein) of coronavirus to the angiotensin-converting enzyme 2 (ACE2) in the host cell is widely considered the first step of infection. However, detailed insights on the underlying mechanism of dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…β-sheet 1 is involved in enhancing the binding after the recognition process. These interactions reinforce the binding between the spike protein of the SARS-CoV-2 and the ACE-2 of the host cell [ 22 ].…”
Section: Furin Is a Masterstroke For Sars-cov-2 Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…β-sheet 1 is involved in enhancing the binding after the recognition process. These interactions reinforce the binding between the spike protein of the SARS-CoV-2 and the ACE-2 of the host cell [ 22 ].…”
Section: Furin Is a Masterstroke For Sars-cov-2 Pathogenesismentioning
confidence: 99%
“…The Epsilon (GH/452R.V1) variant first identified in California, the USA in 2021, showed a 20% increase in transmission possibly attributed to the L452R and D614G substitutions in the spike protein [36]. As of 13th July 2021, cases of Epsilon variant have been reported from 34 nations dominantly in the USA (52,967), Mexico (477), Canada (331), South Korea (109), Aruba (58), Denmark (36), Chile (30), Argentina (28), UK (22), Australia (20), and Colombia (20) (Fig. 5 A) [37].…”
Section: Epsilon (Gh/452rv1)mentioning
confidence: 99%
See 1 more Smart Citation
“…26 Other MD studies concluded that the glycans attached to N90 and N322 of ACE2 could be major determinants of Spike binding, 25 while yet other simulation works postulate that glycosylation does not affect the RBD-ACE2 interaction significantly. 27,28 Genetic or pharmacological blockade of N-glycan biosynthesis at the oligomannose stage in ACE2expressing target cells was found to dramatically reduce viral entry, 29 even though several glycoforms of ACE2 were found to display comparatively moderate variation with respect to Spike binding. 30 Hence, a detailed understanding on how individual glycans on both Spike and ACE2 influence their interaction and a comprehensive experimental validation of the MD findings is crucial for the rational design of novel therapeutic soluble ACE2 variants with enhanced Spike binding affinity and the capacity to block viral entry more efficiently than the native enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…26 Other MD studies concluded that the glycans attached to N90 and N322 of ACE2 could be major determinants of Spike binding, 25 while yet other simulation works postulate that glycosylation does not affect the RBD-ACE2 interaction significantly. 27,28 Genetic or pharmacological blockade of N-glycan biosynthesis at the oligomannose stage in ACE2-expressing target cells was found to dramatically reduce viral entry, 29 even though several glycoforms of ACE2 were found to display comparatively moderate variation with respect to Spike binding. 30 Hence, a detailed understanding on how individual glycans on both Spike and ACE2 influence their interaction and a comprehensive experimental validation of the MD findings is crucial for the rational design of novel therapeutic soluble ACE2 variants with enhanced Spike binding affinity and the capacity to block viral entry more efficiently than the native enzyme.…”
Section: Introductionmentioning
confidence: 99%